The Effect of Torbangun Leaves Tea on Msg-induced Fetal Develop-ment Disorder in Mice (Sumatera Medical Journal, 2019)
The safety of MSG on the fetus has not been confirmed yet. The objective of this research is to determine the effect of tea of torbangun leaves on fetal development disorder of mice. The present study is experimental with a Completely Randomized Design (CRD). Data obtained were then analyzed by ANOVA, with p